Solid superacid catalyst as well as preparation method and application thereof

By introducing Yb3+ and Ce3+ onto a ZrO2-Al2O3 mesoporous support, a solid superacid catalyst was prepared, which solved the problem of catalyst recycling in the hydroxylamine-ester process and improved the efficiency and stability of octanoyl hydroxyxamic acid production.

CN121372447AActive Publication Date: 2026-01-23HAIKE GRP RES INST OF INNOVATION & TECH
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202511982708.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-01-23
Estimated Expiration
2045-12-26

AI Technical Summary

Technical Problem

In existing technologies, the synthesis of octanoyl hydroxamic acid via the hydroxylamine-ester method uses concentrated sulfuric acid catalysts, resulting in high production costs and environmental pollution, and the catalysts are difficult to recycle.

Method used

A solid superacid catalyst was prepared by using a ZrO2 and Al2O3 composite mesoporous support, combined with sulfate and rare earth ions Yb3+ and Ce3+. Rare earth elements were introduced through an integrated synthesis method to form an LDH solid solution, which increased Lewis acid centers and stabilized sulfur species on the catalyst surface.

Benefits of technology

It improved the conversion rate of ethyl octanoate in the preparation of octanoyl hydroxamic acid, extended the catalyst's cycle life, reduced catalyst consumption, and maintained production stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121372447A_ABST
    Figure CN121372447A_ABST
Patent Text Reader

Abstract

The invention discloses a solid superacid catalyst as well as a preparation method and application thereof, and belongs to the technical field of catalyst preparation. The catalyst comprises a mesoporous carrier, sulfate radicals combined on the mesoporous carrier and rare earth ions doped on the mesoporous carrier, wherein the mesoporous carrier is formed by compounding ZrO2 and Al2O3; the rare earth ions are Yb < 3 + > and Ce < 3 + >. The solid superacid catalyst provided by the invention has the advantages that the active components are uniformly dispersed, the catalytic activity is high, the conversion rate of ethyl n-caprylate in a capryloyl hydroximic acid preparation process can be improved, and meanwhile, the cycle service life of the catalyst is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the technical field of catalyst preparation, and particularly relates to a solid superacid catalyst and a preparation method and application thereof. BACKGROUND

[0002] Caprylhydroxamic acid as an ideal organic acid has excellent antibacterial and bacteriostatic performance at neutral pH value, can be used in a chemical preservative-free formula system, and is compatible with most raw materials, is not affected by surfactants, proteins and other raw materials in the system, can be compounded with alcohol, diol and other preservatives, and is a safe and efficient preservative.

[0003] There are many methods for synthesizing caprylhydroxamic acid, but the most important synthesis routes on the market at present are divided into two kinds: hydroxylamine-ester method and hydroxylamine-acyl chloride method. The hydroxylamine-acyl chloride method has the disadvantages of large viscosity and poor flowability after acyl chloride of fatty acid, generation of a large amount of acid gas, easy corrosion of equipment and serious pollution of the environment. The hydroxylamine-ester method is the current mainstream synthesis method. The hydroxylamine-ester method first uses n-octanoic acid and methanol / ethanol for esterification reaction to generate capryl methyl / ethyl ester, and then the synthesized capryl ester is subjected to hydroxylamine reaction with hydroxylamine salt to synthesize the final caprylhydroxamic acid. The n-octanoic acid esterification reaction for synthesizing capryl ethyl ester mainly uses concentrated sulfuric acid as a catalyst, for example, in the patent CN110845367B, n-octanoic acid and ethanol are used for preparing n-octanoic acid ethyl ester under the catalysis of sulfuric acid by heating reflux, but the concentrated sulfuric acid cannot be reused, a large amount of wastewater is generated in the reaction, the production cost is greatly increased, and environmental pollution is caused. Therefore, it is of great significance to develop a catalyst with high activity and good stability to improve the recycling efficiency of the catalyst. SUMMARY

[0004] In view of the deficiencies in the prior art, the present application provides a solid superacid catalyst and a preparation method and application thereof. The solid superacid catalyst provided in the present application has uniformly dispersed active components and high catalytic activity, can improve the conversion rate of n-octanoic acid ethyl ester in the preparation process of caprylhydroxamic acid, and prolongs the service life of the catalyst.

[0005] To solve the technical problem, the present application provides a solid superacid catalyst, which comprises a mesoporous carrier, sulfate combined on the mesoporous carrier and rare earth ions doped on the mesoporous carrier, wherein the mesoporous carrier is composed of ZrO2 and Al2O3; the rare earth ions are Yb 3+ and Ce 3+ ; the molar ratio of ZrO2 to Al2O3 is 2-6:1; the molar ratio of Yb 3+ and Ce 3+ is 0.8-2.5:1; and the molar ratio of Al2O3 to Yb 3+ is 2.5-8:1.

[0006] The application provides a preparation method of the solid superacid catalyst, and comprises the following steps: 1) a mixed solution of aluminum nitrate, ytterbium nitrate, cerium nitrate and a template agent is prepared, and is denoted as solution A; a mixed solution of zirconium n-propylate and acetylacetone is prepared, and is denoted as solution B; a mixed solution of solution B and deionized water is added into solution A under stirring to obtain a mixed solution; 2) the pH value of the obtained mixed solution is adjusted to 5-6 for aging to obtain a gel; 3) the obtained gel is sequentially added into an alkaline solution for refluxing, washing, drying and grinding to obtain a powder; the alkaline solution comprises NaOH, KOH, ammonia water, Na2CO3 and NaHCO3 solution; 4) the obtained powder is calcined to obtain a ZrO2-Al2O3 powder doped with rare earth ions; 5) the ZrO2-Al2O3 powder doped with rare earth ions is immersed in a sulfuric acid solution, and then stirring, filtering, drying and calcining are sequentially performed on the obtained filter cake to obtain the solid superacid catalyst.

[0007] Preferably, the temperature of the aging in step 2) is 45-80 ℃, and the aging time is 6-48 h.

[0008] Preferably, the temperature of the calcining in step 4) is 200-800 ℃, and the calcining time is 3-8 h.

[0009] Preferably, the temperature of the drying in step 5) is 80-130 ℃, and the drying time is 12-24 h; the temperature of the calcining is 400-800 ℃, and the calcining time is 3-8 h.

[0010] The application provides an application of the solid superacid catalyst in synthesis of octanoyl hydroxamic acid. (1) n-octanoic acid, ethanol and the solid superacid catalyst are mixed, the obtained mixed solution is reacted, and the reaction solution is distilled under reduced pressure to obtain ethyl n-octanoate; (2) hydroxylamine salt and a solid base are uniformly mixed in an ethanol solvent, and then the above ethyl n-octanoate is added to react to obtain octanoyl hydroxamic acid.

[0011] Preferably, the addition amount of the catalyst in step (1) is 1wt%-10wt% of the n-octanoic acid.

[0012] Preferably, the molar ratio of the n-octanoic acid to the ethanol in step (1) is 1:1-1.5.

[0013] Compared with the prior art, the application has the beneficial effects that: The solid superacid catalyst provided by the present application takes ZrO2 and Al2O3 as carriers, and introduces Yb and Ce, which not only helps to increase Lewis acid centers, but also helps to stabilize sulfur species on the surface of the catalyst, and shows significant synergistic effect to affect the acid properties of the catalyst surface and the interaction between the sulfate species and the carrier, so that the catalyst prepared by the preparation method of the present application has good catalytic activity and stability, effectively reduces the catalyst consumption in the preparation step of ethyl n-octanoate, and maintains the stable production of octanoyl hydroxamic acid. BRIEF DESCRIPTION OF DRAWINGS

[0014] Figure 1 The SEM image of the catalyst prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0015] The technical solutions in the specific embodiments of the present application will be described in detail below. Obviously, the described embodiments are only part of the specific embodiments of the general technical solution of the present application, but not all the embodiments. Based on the general concept of the present application, all other embodiments obtained by those skilled in the art fall within the scope of protection of the present application.

[0016] The present application provides a solid superacid catalyst, which comprises a mesoporous carrier, sulfate combined on the mesoporous carrier and rare earth ions doped on the mesoporous carrier, wherein the mesoporous carrier is composed of ZrO2 and Al2O3; and the rare earth ions are Yb 3+ and Ce 3+ In the present application, the molar ratio of ZrO2 to Al2O3 is 2-6:1. The molar ratio of Yb 3+ and Ce 3+ is 1-2:1; and the molar ratio of Al2O3 to Yb 3+ is 5-20:1.

[0017] The solid superacid catalyst provided by the present application introduces Yb and Ce, which not only helps to increase Lewis acid centers, but also helps to stabilize sulfur species on the surface of the catalyst, and shows significant synergistic effect to affect the acid properties of the catalyst surface and the interaction between the sulfate species and the carrier, so that the catalyst prepared by the preparation method of the present application has good catalytic activity and stability, effectively reduces the catalyst consumption in the preparation step of ethyl n-octanoate, and maintains the stable production of octanoyl hydroxamic acid.

[0018] The present application provides a preparation method of the above-mentioned solid superacid catalyst, which comprises the following steps: 1) a mixed solution of aluminum nitrate, ytterbium nitrate, cerium nitrate and a template agent is prepared, denoted as solution A; a mixed solution of zirconium n-propyl alcohol and acetylacetone is prepared, denoted as solution B; the mixed solution of solution B and deionized water is added to solution A under stirring to obtain a mixed solution; 2) the pH value of the obtained mixed solution is adjusted to 5-6 for aging to obtain a gel; 3) the obtained gel is sequentially added to an alkaline solution for refluxing, washing, drying and grinding to obtain a powder; 4) the obtained powder is calcined to obtain a ZrO2-Al2O3 powder doped with rare earth ions; 5) the ZrO2-Al2O3 powder doped with rare earth ions is immersed in a sulfuric acid solution, stirred, filtered, and the obtained filter cake is sequentially dried and calcined to obtain a solid superacid catalyst.

[0019] In the present application, a mixed solution of aluminum nitrate, ytterbium nitrate, cerium nitrate and a template agent is prepared, denoted as solution A; a mixed solution of zirconium n-propyl alcohol and acetylacetone is prepared, denoted as solution B; the mixed solution of solution B and deionized water is added to solution A under stirring to obtain a mixed solution. In the present application, the template agent is preferably a surfactant template such as Pluronic F127, Pluronic P123, PEI (polyethyleneimine), CTAB (hexadecyl trimethyl ammonium bromide), SDS (sodium dodecyl sulfonate), polyoxyethylene sorbitan ester, glucose, maltose, urea, tartaric acid derivatives, polyethylene glycol, microemulsion and emulsion.

[0020] After obtaining the mixed solution, the pH value of the obtained mixed solution is adjusted to 5-6 for aging to obtain a gel. In the present application, the temperature of the aging is preferably 45-80°C, and the time of the aging is preferably 6-48h.

[0021] After obtaining the gel, the obtained gel is sequentially added to an alkaline solution for refluxing, washing, drying and grinding to obtain a powder. In the present application, the alkaline solution includes NaOH, KOH, ammonia water, Na2CO3, NaHCO3 solution; the concentration of the alkaline solution is preferably 0.2-5 mol / L; the time of the refluxing is preferably 24h. In the present application, deionized water with a solid mass of 2-5 times is preferably used for washing to remove excess metal ions. In the present application, after the washing is completed, a conductivity meter is preferably used for determination, so that the conductivity is kept at 0-1.0 mS / cm. In the present application, the temperature of the drying is preferably 60-120°C, and the time is preferably 8-24h.

[0022] After obtaining the powder, the present application calcines the obtained powder to obtain ZrO2-Al2O3 powder doped with rare earth ions. In the present application, the temperature of the calcination is preferably 200-800℃, more preferably 300-700℃, and most preferably 450-580℃; the time of the calcination is preferably 3-8h.

[0023] After obtaining the ZrO2-Al2O3 powder doped with rare earth ions, the present application dips the ZrO2-Al2O3 powder doped with rare earth ions in a sulfuric acid solution, stirs, filters, and sequentially dries and calcines the obtained filter cake to obtain a solid superacid catalyst. In the present application, the dipping method includes but is not limited to over-dipping, equal-volume dipping, multiple-dipping, dipping and precipitation, fluidized spray dipping, and vapor-phase dipping. In the present application, the concentration of the sulfuric acid solution is preferably 0.2-1.0mol / L, and the stirring time is preferably 6-18h. The temperature of the drying is preferably 80-130℃, and the time is preferably 12-24h. In the present application, the temperature of the calcination is preferably 400-800℃, more preferably 500-600℃; and the time of the calcination is preferably 3-12h.

[0024] The present application provides a preparation method of a solid superacid catalyst, which is prepared by using an integrated synthesis method. In the preparation of ZrO2-Al2O3, rare earth elements Yb and Ce are added, so that a rare earth-doped LDH solid solution, i.e., Yb 3+ , Ce 3+ partially replaces Zr 4+ or Al 3+ in the layer plate, introduces imbalance of lattice charge, and fundamentally changes the structural stability and surface acidity and alkalinity of the catalyst.

[0025] In the present application, five Hammett acid indicators are preferably used to determine the acidity of the solid superacid catalyst: (1) the discoloration reaction of p-nitrotoluene (acid strength (H0=-11.35), (2) m-nitrotoluene (H0=-11.99), (3) p-nitrochlorobenzene (H0=-12.70), (4) 2,4-dinitrotoluene (H0=-13.75), and (5) 24-dinitrofluorobenzene (H0=-14.52) are used to determine the acid strength of the catalyst.

[0026] The present application provides the use of the above-mentioned solid superacid catalyst in the synthesis of octanoyl hydroxamic acid, which is synthesized by the following steps: (1) mixing n-octanoic acid, ethanol and the solid superacid catalyst, reacting the obtained mixture, and distilling the reaction liquid under reduced pressure to obtain ethyl n-octanoate; (2) After hydroxylamine salt and solid base are mixed uniformly in ethanol solvent, the above octanoic acid ethyl ester is added to react, and octanoyl hydroxamic acid is obtained.

[0027] In the present application, the molar ratio of the octanoic acid and ethanol is preferably 1:1-1.5. In the present application, the catalyst is preferably added in an amount of 1wt%-10wt% of the octanoic acid, more preferably 4wt%-8wt%. In the present application, the reaction temperature is preferably 50-150℃, more preferably 60-100℃, and most preferably 80-90℃; the reaction time is preferably 2-20h, more preferably 5-10h, and most preferably 7-10h. In the present application, the pressure during the reduced pressure distillation is preferably 0.003-0.01MPa, and the temperature is preferably 80-120℃.

[0028] After the octanoic acid ethyl ester is obtained, hydroxylamine salt and solid base are mixed uniformly in ethanol solvent, and the above octanoic acid ethyl ester is added to react, and octanoyl hydroxamic acid is obtained. In the present application, the hydroxylamine salt is preferably hydroxylamine hydrochloride or hydroxylamine sulfate; and the solid base is preferably sodium carbonate, sodium bicarbonate, sodium hydroxide or sodium methoxide. In the present application, the molar ratio of the octanoic acid ethyl ester to the hydroxylamine salt and the solid base is 1:1-2:1-2. In the present application, the mass ratio of the octanoic acid ethyl ester to the ethanol solvent is preferably 1:4-9. In the present application, the reaction temperature is preferably 10-50℃, more preferably 10-40℃, and most preferably 20-30℃; and the reaction time is preferably 1-5h. In the present application, after the reaction is completed, it preferably further includes filtration, removal of the solvent by reduced pressure distillation, crystallization by adding water and adjusting the pH to 6-7, filtration and drying to obtain octanoyl hydroxamic acid.

[0029] In order to further illustrate the present application, the technical solutions provided by the present application are described in detail below in conjunction with examples, but they should not be understood as limiting the scope of protection of the present application.

[0030] Example 1 Take 20 g of Pluronic F127, 37.5 g of Al (NO3) 3-9H2O, 4.49 g of Yb (NO3) 3-6H2O, 4.78 g of Ce (NO3) 3-3H2O, dissolve them in 500 mL of anhydrous ethanol and stir for 30 min, and mark it as solution A. Take 163.8 g of zirconium n-propylate (Zr (OPr) 4) (the n-propyl alcohol in zirconium n-propylate is 60 wt.%) and 8.7 g of acetylacetone, mix them and then dissolve them in 320 mL of anhydrous ethanol, mark it as solution B. Slowly drop the mixed solution of solution B and 32 mL of water into solution A under vigorous stirring, adjust the pH to 5, age at 60℃ for 24 h, and then reflux the obtained sol in 1 mol / L NaOH solution for 24 h. Subsequently, remove the excess Na ions with deionized water and dry at 80℃ overnight. Then grind it into a solid powder and put it into a muffle furnace, and raise the temperature to 580℃ at a temperature rising speed of 10℃ / min, and keep it for 8 h to obtain Yb, Ce doped ZrO2-Al2O3.

[0031] Take 5 g of ZrO2-Al2O3 powder and immerse it in 100 mL of 0.5 mol / L sulfuric acid solution, stir for 12 h and then filter, dry the obtained filter cake at 120℃ for 12 h, and then calcine it in a muffle furnace at 500℃ for 5 h to obtain a solid superacid catalyst SO4 2- / ZrO2-Al2O3 (Zr / Al = 2:1), marked as catalyst 1. The SEM image of the catalyst is shown in Figure 1 The obtained catalyst was subjected to acid determination by Hammett acid indicator method, and the acid strength H0 of the catalyst was obtained to be <-12.70, which has reached the superacid level.

[0032] Example 2 The difference between Example 2 and Example 1 is that the amount of Al (NO3) 3-9H2O is added according to the molar ratio Zr / Al = 3:1, and the other steps are the same as the preparation method of Example 1. The specific operation is as follows: Take 20 g of Pluronic F127, 56.25 g of Al (NO3) 3-9H2O, 4.49 g of Yb (NO3) 3-6H2O, 4.78 g of Ce (NO3) 3-3H2O, and dissolve them in 500 mL of anhydrous ethanol and stir for 30 min, and mark it as solution A. Take 163.8 g of zirconium n-propylate (Zr (OPr) 4) (the n-propyl alcohol in zirconium n-propylate is 60 wt.%) and 8.7 g of acetylacetone, and dissolve them in 320 mL of anhydrous ethanol, and mark it as solution B. Slowly drop the mixed solution of solution B and 32 mL of water into solution A under vigorous stirring, adjust the pH to 5, and age at 60°C for 24 h, and then reflux the obtained sol in 1 mol / L NaOH solution for 24 h. Subsequently, remove the excess Na ions with deionized water, and dry at 80°C overnight. Then grind it into a solid powder, and then put it into a muffle furnace, and raise the temperature to 580°C at a temperature raising speed of 10°C / min, and keep it for 8 h, to obtain Yb, Ce doped ZrO2-Al2O3.

[0033] Take 5 g of ZrO2-Al2O3 powder and immerse it in 100 mL of 0.5 mol / L sulfuric acid solution, stir for 12 h, and then filter, and dry the obtained filter cake at 120°C for 12 h, and then put it into a muffle furnace and calcine it at 500°C for 5 h, to obtain a solid superacid catalyst SO4 2- / ZrO2-Al2O3 (Zr / Al = 3:1), and mark it as catalyst 2. The obtained catalyst is subjected to acid determination by Hammett acid indicator method, and the acid strength H0 of the catalyst is <-12.70, which has reached the superacid level.

[0034] Example 3 The difference between Example 3 and Example 1 is that the amount of Al (NO3) 3-9H2O is added according to the molar ratio Zr / Al = 1:1, and the other steps are the same as the preparation method of Example 1. The specific operation is as follows: Take 20 g of Pluronic F127, 18.75 g of Al(NO3)3·9H2O, 4.49 g of Yb(NO3)3·6H2O, 4.78 g of Ce(NO3)3·3H2O, and stir in 500 mL of anhydrous ethanol for 30 min, and mark it as solution A. Take 163.8 g of zirconium n-propylate (Zr(OPr)4) (the n-propyl alcohol in zirconium n-propylate is 60 wt.%) and 8.7 g of acetylacetone, and dissolve them in 320 mL of anhydrous ethanol, and mark it as solution B. Slowly drop the mixed solution of solution B and 32 mL of water into solution A under vigorous stirring, adjust the pH to 5, and age at 60°C for 24 h, and then reflux the obtained sol in a 1 mol / L NaOH solution for 24 h. Subsequently, remove the excess Na ions with deionized water, and dry at 80°C overnight. Then grind it into a solid powder, and then put it into a muffle furnace, and raise the temperature to 580°C at a temperature raising speed of 10°C / min, and keep it for 8 h, to obtain Yb, Ce doped ZrO2-Al2O3.

[0035] Take 5 g of ZrO2-Al2O3 powder, and immerse it in 100 mL of a 0.5 mol / L sulfuric acid solution, and stir for 12 h, and then filter, and dry the obtained filter cake at 120°C for 12 h, and then calcine it in a muffle furnace at 500°C for 5 h, to obtain a solid superacid catalyst SO4 2- / ZrO2-Al2O3 (Zr / Al = 1:1), and mark it as catalyst 3. The obtained catalyst is subjected to acid determination by the Hammett acid indicator method, and the acid strength H0 of the catalyst is obtained to be <-12.70, which has reached the superacid level.

[0036] Example 4 Take 20 g of Pluronic F127, 37.5 g of Al(NO3)3·9H2O, 6.74 g of Yb(NO3)3·6H2O, 4.78 g of Ce(NO3)3·3H2O, and stir in 500 mL of anhydrous ethanol for 30 min, and mark it as solution A. Take 163.8 g of zirconium n-propylate (Zr(OPr)4) (the n-propyl alcohol in zirconium n-propylate is 60 wt.%) and 8.7 g of acetylacetone, and dissolve them in 320 mL of anhydrous ethanol, and mark it as solution B. Slowly drop the mixed solution of solution B and 32 mL of water into solution A under vigorous stirring, adjust the pH to 5, and age at 80°C for 6 h, and then reflux the obtained sol in a 1 mol / L NaOH solution for 24 h. Subsequently, remove the excess Na ions with deionized water, and dry at 80°C overnight. Then grind it into a solid powder, and then put it into a muffle furnace, and raise the temperature to 800°C at a temperature raising speed of 10°C / min, and keep it for 4 h, to obtain Yb, Ce doped ZrO2-Al2O3.

[0037] 5 g of ZrO2-Al2O3 powder was impregnated in 100 mL of 0.5 mol / L sulfuric acid solution, stirred for 12 h, and then filtered. The resulting filter cake was dried at 120 °C for 12 h and then calcined in a muffle furnace at 400 °C for 8 h to obtain a solid superacid catalyst SO4. 2- The catalyst, denoted as catalyst 4, is a mixture of ZrO2-Al2O3 (Zr / Al = 2:1). The acidity of the catalyst was determined using the Hammett acid indicator method, and the acid strength H0 < -12.70, indicating it reaches the level of a superacid.

[0038] Example 5 20 g of Pluronic F127, 37.5 g of Al(NO3)3·9H2O, 8.98 g of Yb(NO3)3·6H2O, and 3.18 g of Ce(NO3)3·3H2O were dissolved in 500 mL of anhydrous ethanol and stirred for 30 min, and this solution was designated as solution A. 163.8 g of zirconium propoxide (Zr(OPr)4) (in which n-propanol is 60 wt.%) and 8.7 g of acetylacetone were dissolved in 320 mL of anhydrous ethanol, and this solution was designated as solution B. A mixture of solution B and 32 mL of water was slowly added dropwise to solution A under vigorous stirring. The pH was adjusted to 6, and the solution was aged at 45 °C for 48 h. The resulting sol was then refluxed in 1 mol / L NaOH solution for 24 h. Subsequently, excess Na ions were removed with deionized water, and the sol was dried overnight at 80 °C. Then, it was ground into a solid powder and placed in a muffle furnace, heated to 300℃ at a heating rate of 10℃ / min, and held for 8 h to obtain Yb and Ce doped ZrO2-Al2O3.

[0039] 5 g of ZrO2-Al2O3 powder was impregnated in 100 mL of 0.5 mol / L sulfuric acid solution, stirred for 12 h, and then filtered. The resulting filter cake was dried at 120 °C for 12 h and then calcined in a muffle furnace at 800 °C for 3 h to obtain a solid superacid catalyst SO4. 2- The catalyst, denoted as catalyst 5, is a mixture of ZrO2-Al2O3 (Zr / Al = 2:1). The acidity of the catalyst was determined using the Hammett acid indicator method, and the acid strength H0 < -12.70, indicating it reaches the level of a superacid.

[0040] Example 6 (1) Preparation of ethyl octanoate Mix 43.26 g of n-octanoic acid and 17.97 g of anhydrous ethanol in a 250 ml three-necked flask, then add 2.2 g of catalyst 1, heat to reflux at 85°C for 5 h. After the reaction is completed, the reaction liquid is cooled, the catalyst is separated from the reaction liquid, and the reaction liquid is distilled under reduced pressure (pressure is 0.01 MPa, temperature is 120°C) to obtain 48.25 g of colorless liquid product. Gas chromatography analysis shows that the purity of the liquid product is 99.3% and the yield is 89.7%.

[0041] (2) Preparation of octanoyl hydroxamic acid In a 250 ml three-necked flask, add 120.8 g of ethanol, then add 7.69 g (0.11 mol, 1.1 eq) of hydroxylamine hydrochloride and 6.8 g of solid base (solid base is sodium hydroxide) catalyst, mix uniformly, then add 17.23 g (0.1 mol, 1.0 eq) of ethyl octanoate synthesized above, react at 35°C for 1.5 h, filter, remove the ethanol aqueous solution by distillation under reduced pressure, then add 80 ml of deionized water, slowly drop the hydrochloric acid below 5°C, adjust the pH to 4, precipitate white solid, filter and wash with water, dry to obtain 13.25 g of white solid, which is octanoyl hydroxamic acid product, purity is 99.5%, yield is 87.5%.

[0042] Comparative Example 1 Take 20 g of Pluronic F127, 37.5 g of Al(NO3)3·9H2O is dissolved in 500 mL of anhydrous ethanol and stirred for 30 min, marked as solution A. Take 163.8 g of zirconium n-propyl alcohol (Zr(OPr)4) (60 wt.% n-propyl alcohol) and 8.7 g of acetylacetone are dissolved in 320 mL of anhydrous ethanol, marked as solution B. The mixed solution of solution B and 32 mL of water is slowly added to solution A under vigorous stirring, adjust the pH to 5, and age at 60°C for 24 h, then the obtained sol is refluxed in 1 mol / L NaOH solution for 24 h. Subsequently, the excess Na ions are removed with deionized water and dried at 80°C overnight. Then it is ground into a solid powder and placed in a muffle furnace, with a temperature rising rate of 10°C / min, to 580°C, and kept for 8 h to obtain ZrO2-Al2O3.

[0043] Take 5 g of ZrO2-Al2O3 powder and immerse it in 100 mL of 0.5 mol / L sulfuric acid solution, stir for 12 h, then filter, dry the filter cake at 120°C for 12 h, then calcine it in a muffle furnace at 500°C for 5 h to obtain solid superacid catalyst SO4 2-ZrO2-Al2O3(Zr / Al = 2:1), denoted as Catalyst 6. The resulting catalyst was measured for its acidity using the Hammett acidity indicator method, and the acid strength of the catalyst was found to be H0<-12.70, which is in the superacid category.

[0044] Comparative Example 2 Take 20 g of Pluronic F127, 37.5 g of Al(NO3)3-9H2O, 4.78 g of Ce(NO3)3-3H2O, and stir for 30 min in 500 mL of anhydrous ethanol, denoted as solution A. Take 163.8 g of zirconium n-propyl alcohol (Zr(OPr)4) (n-propyl alcohol in zirconium n-propyl alcohol is 60 wt.%) and 8.7 g of acetylacetone and dissolve in 320 mL of anhydrous ethanol, denoted as solution B. Slowly drop the mixed solution of solution B and 32 mL of water into solution A under vigorous stirring, adjust the pH to 5, age at 60°C for 24 h, then reflux the resulting sol in 1 mol / L NaOH solution for 24 h. Subsequently, remove excess Na ions with deionized water, dry at 80°C overnight. Then grind it into a solid powder and put it into a muffle furnace, with a temperature rising rate of 10°C / min, to 580°C, and keep for 8 h, to obtain Ce-doped ZrO2-Al2O3.

[0045] Take 5 g of ZrO2-Al2O3 powder and immerse it in 100 mL of 0.5 mol / L sulfuric acid solution, stir for 12 h, then filter, dry the filter cake at 120°C for 12 h, then place it in a muffle furnace and calcine at 500°C for 5 h, to obtain a solid superacid catalyst SO4 2- ZrO2-Al2O3(Zr / Al = 2:1), denoted as Catalyst 7. The resulting catalyst was measured for its acidity using the Hammett acidity indicator method, and the acid strength of the catalyst was found to be H0<-12.70, which is in the superacid category.

[0046] Comparative Example 3 The difference between Example 1 and Comparative Example 3 is that Yb(NO3)3-6H2O and Ce(NO3)3-3H2O are directly impregnated into the carrier, and the other operations are exactly the same as Example 1, and the specific operation is as follows: Take 20 g Pluronic F127, 37.5 g Al (NO3) 3.9H2O is dissolved in 500 mL of anhydrous ethanol and stirred for 30 min, recorded as solution A. Take 163.8 g of zirconium n-propyl alcohol (Zr (OPr) 4) (60 wt.% n-propyl alcohol) and 8.7 g acetylacetone is dissolved in 320 mL of anhydrous ethanol, recorded as solution B. The mixed solution of solution B and 32 mL of water is slowly added to solution A under vigorous stirring, adjust the pH to 5, aging at 60℃ for 24 h, then the obtained sol is refluxed in 1 mol / L NaOH solution for 24 h. Subsequently, the excess Na ion is removed with deionized water, dried at 80℃ overnight, then it is ground into a solid powder. Take a mixed solution of 4.49 g Yb (NO3) 3, 4.78 g Ce (NO3) 3.3H2O by equal volume impregnation method on the solid powder, then put it into the muffle furnace to rise to 580℃ at a temperature rising rate of 10℃ / min, keep for 8 h, get Yb, Ce doped ZrO2-Al2O3.

[0047] Take 5 g of ZrO2-Al2O3 powder is impregnated in 100 mL of 0.5 mol / L sulfuric acid solution, after stirring for 12 h, filter, the obtained filter cake is dried at 120℃ for 12 h, then placed in the muffle furnace at 500℃ for calcination for 5 h, get solid super acid catalyst SO4 2- / ZrO2-Al2O3 (Zr / Al = 2:1), recorded as catalyst 8. The SEM image of the catalyst is shown in Figure 1 The obtained catalyst is determined by Hammett acid indicator method, the acid strength H0 of the catalyst is <-12.70, which has reached the super acid level.

[0048] Example 7 The catalysts prepared in examples 1-5 and comparative examples 1-3 are used for the synthesis of ethyl octanoate by the reaction of n-octanoic acid and ethanol, the specific reaction parameters and results are shown in Table 1.

[0049] Table 1

[0050] Example 8 Mix 43.26 g of n-octanoic acid and 17.97 g of anhydrous ethanol in a 250 ml three-necked flask, then add 2.2 g of catalyst 1, heat to reflux at 85℃ for 5 h. After the reaction is completed, the catalyst is separated from the reaction liquid, the reaction liquid is treated according to the step (1) in example 7, the catalyst is washed and calcined, and reserved for the second batch. According to the feeding ratio of the first batch, the second batch of reaction raw materials is put into the three-necked flask, and the second batch of reaction is started, and the following batches of reaction are carried out in turn. The effect of the number of times of using the catalyst on the reaction is investigated, and the results are shown in Table 2.

[0051] Table 2

[0052] As can be seen from Table 2, after multiple cycles, the conversion rate of n-octanoic acid and the yield of ethyl octanoate are basically stable, indicating that the catalyst prepared by the present application has good stability and long service life.

Claims

1. A solid superacid catalyst, characterized in that, The catalyst comprises a mesoporous support, sulfate ions bound to the mesoporous support, and rare earth ions doped onto the mesoporous support. The mesoporous support is composed of ZrO2 and Al2O3. The rare earth ions are Yb. 3+ and Ce 3+ The molar ratio of ZrO2 to Al2O3 is 2-6:1; the Yb 3+ and Ce 3+ The molar ratio of Al₂O₃ to Yb is 0.8-2.5:

1. 3+ The molar ratio is 2.5-8:

1.

2. The method for preparing the solid superacid catalyst according to claim 1, characterized in that, Includes the following steps: 1) Prepare a mixed solution of aluminum nitrate, ytterbium nitrate, cerium nitrate and template agent, denoted as solution A; prepare a mixed solution of zirconium propoxide and acetylacetone, denoted as solution B; add the mixture of solution B and deionized water to solution A under stirring to obtain a mixed solution; 2) Adjust the pH of the obtained mixed solution to 5-6 and age it to obtain a gel; 3) The obtained gel is added to an alkaline solution in sequence for reflux, washing, drying and grinding to obtain powder; the alkaline solution includes NaOH, KOH, ammonia, Na2CO3 and NaHCO3 solutions; 4) The obtained powder is calcined to obtain rare earth ion-doped ZrO2-Al2O3 powder; 5) The ZrO2-Al2O3 powder doped with rare earth ions was impregnated in sulfuric acid solution, stirred, filtered, and the resulting filter cake was dried and calcined in sequence to obtain a solid superacid catalyst.

3. The preparation method according to claim 2, characterized in that, The aging temperature described in step 2) is 45-80℃, and the aging time is 6-48h.

4. The preparation method according to claim 2, characterized in that, The calcination temperature in step 4) is 200-800℃, and the time is 3-8h.

5. The preparation method according to claim 2, characterized in that, The drying temperature in step 5) is 80-130℃ and the time is 12-24h; the calcination temperature is 400-800℃ and the time is 3-8h.

6. The application of the solid superacid catalyst according to claim 1 in the synthesis of octanoyl hydroxamic acid, characterized in that, Octanoyl hydroxamic acid was synthesized using the following steps: (1) Mix octanoic acid, ethanol and solid superacid catalyst, react the resulting mixture, and distill the reaction solution under reduced pressure to obtain ethyl octanoate; (2) After adding hydroxylamine salt and solid base to ethanol solvent and mixing them evenly, add the above-mentioned ethyl octanoate to react and obtain octanoyl hydroxamic acid.

7. The application according to claim 6, characterized in that, The amount of catalyst added in step (1) is 1wt%-10wt% of octanoic acid.

8. The application according to claim 6, characterized in that, The molar ratio of octanoic acid and ethanol in step (1) is 1:1-1.5.

Citation Information

Patent Citations

  • Solid catalyst and preparation method therefor

    CN106563448A

  • Synthesizing method of acetylsalicylic acid

    CN109369395A

  • Application of superacid catalyst in direct synthesis of adiponitrile from adipic acid

    CN111250113A

  • Preparation method of three-way catalyst for automobile exhaust and product and application thereof

    CN111921540A

  • Catalyst for dehydration of 2-alcohol, preparation method of catalyst and method for preparing alpha-olefin by dehydration of 2-alcohol

    CN116037096A